THE RELATIONSHIP OF THE ENVIRONMENT WITH THE DEVELOPMENT OF THE STATE'S ECONOMY. - Egamberdiev Shavkatbek Shahabiddinovich (Scholar Express Journals, 2024)
Over the past few decades, economic growth has put severe pressure on the environment in the form of increased CO2 emissions, depletion of natural resources and climate change. Studying the relationship between environmental quality and economic development will be useful for policy makers to develop and implement effective policies to achieve the Sustainable Development Goals. The relationship of economic growth with the environment and vice versa is best explained by the Kuznets Ecological curve (EKC), which shows that environmental degradation in the early stages of growth increases, but decreases when the income threshold exceeds the value. This article aims to explain the role of natural resources in supporting economic growth and provides a literary overview of various studies of the ULC hypothesis.
Keywords: CO2; emissions; growth; environment